Implementasi Nilai Moderasi Beragama pada Tradisi Satu Tungku Tiga Batu dalam Konseling Keluarga Islam - Mita Putri Apriliani; Ema Hidayanti; Abdul Karim; Widayat Mintarsih (Journal of Society Counseling, 2026)
This study examines the implementation of religious moderation values in Islamic family counseling practices rooted in the local wisdom of Satu Tungku Tiga Batu in Kampung Patipi Pulau, Fakfak Regency. A descriptive qualitative approach was employed, with data collected through field observations, in-depth interviews with a religious leader (Jufri) and a traditional as well as government figure (Sudin Bauw), documentation of community social practices, and content analysis of a BBC News video highlighting interfaith coexistence in Fakfak. Data were analyzed using directed content analysis with predetermined coding categories, namely justice, balance, and tolerance. The findings indicate that the value of justice is implemented through deliberative counseling practices that provide equal participation opportunities for all family members, regardless of religious background or clan affiliation. Balance is reflected in the proportional distribution of family roles and emotional regulation within family relationships. Meanwhile, tolerance is manifested through acceptance of religious differences and the maintenance of kinship ties across faiths. These practices are strengthened by the integration of Islamic values and the philosophy of Satu Tungku Tiga Batu, which functions as an ethical and cultural framework in family guidance. This study concludes that Islamic family counseling in Kampung Patipi Pulau operates contextually through cultural mediation and contributes to the development of culturally grounded religious moderation.